LncRNA Nostrill promotes interferon-γ-stimulated gene transcription and facilitates intestinal epithelial cell-intrinsic anti-Cryptosporidium defense - Sharmin, Zinat; Jin, Kehua; Gong, Ai-Yu; Deng, Silu; Pok, Chansorena; Graham, Marion L.; Wang, Shuhong; Mathy, Nicholas W.; Shibata, Annemarie; Chen, Xian-Ming (Frontiers in Immunology, 2024)
Intestinal epithelial cells possess the requisite molecular machinery to initiate cell-intrinsic defensive responses against intracellular pathogens, including intracellular parasites. Interferons (IFNs) have been identified as cornerstones of epithelial cell-intrinsic defense against such pathogens in the gastrointestinal tract. Long non-coding RNAs (lncRNAs) are RNA transcripts (>200 nt) not translated into protein and represent a critical regulatory component of mucosal defense. We report here that lncRNA Nostrill facilitates IFN-γ-stimulated intestinal epithelial cell-intrinsic defense against infection by Cryptosporidium, an important opportunistic pathogen in AIDS patients and a common cause of diarrhea in young children. Nostrill promotes transcription of a panel of genes controlled by IFN-γ through facilitating Stat1 chromatin recruitment and thus, enhances expression of several genes associated with cell-intrinsic defense in intestinal epithelial cells in response to IFN-γ stimulation, including Igtp, iNos, and Gadd45g. Induction of Nostrill enhances IFN-γ-stimulated intestinal epithelial defense against Cryptosporidium infection, which is associated with an enhanced autophagy in intestinal epithelial cells. Our findings reveal that Nostrill enhances the transcription of a set of genes regulated by IFN-γ in intestinal epithelial cells. Moreover, induction of Nostrill facilitates the IFN-γ-mediated epithelial cell-intrinsic defense against cryptosporidial infections.